The last flight : a novel - Clark, Julie, 1971- (Sourcebooks Landmark, 2020)
"Claire Cook has a perfect life. Married to the scion of a political dynasty, with a Manhattan townhouse and a staff of ten, her surroundings are elegant, her days flawlessly choreographed, and her future auspicious. But behind closed doors, nothing is quite as it seems. That perfect husband has a temper that burns as bright as his promising political career, and he's not above using his staff to track Claire's every move, making sure she's living up to his impossible standards. But what he doesn't know is that Claire has worked for months on a plan to vanish. A chance meeting in an airport bar brings her together with a woman whose circumstances seem equally dire. Together they make a last-minute decision to switch tickets - Claire taking Eva's flight to Oakland, and Eva traveling to Puerto Rico as Claire. They believe the swap will give each of them the head start they need to begin again somewhere far away. But when the flight to Puerto Rico goes down, Claire realizes it's no longer a head start but a new life. Cut off, out of options, with the news of her death about to explode in the media, Claire will assume Eva's identity, and along with it, the secrets Eva fought so hard to keep hidden."--Publisher.